1995
DOI: 10.1203/00006450-199512000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pulmonary Neutrophils in the Adult and Neonatal Rat after Hyperoxia

Abstract: The mechanisms of the increased tolerance to hyperoxia of neonatal animals of many species is incompletely understood. To investigate the etiology of this difference we compared neutrophi1 entry into the lungs of neonatal and adult rats after hyperoxic exposure. Adult rats were studied after exposure to 298% 0, for 60 h and neonatal rats after 3 and 7 d. Neonatal survival was prolonged compared with that reported for adult rats (77% after 7 d of exposure). In adult rats, there were significant increases in pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…Our findings of a significant increase in neutrophil infiltration in hyperoxia-exposed mice complement and extend the conclusions of other studies that found that high concentrations of oxygen led to the release of reactive oxygen species that promoted neutrophil infiltration into the lung (41,42). Lungs taken from multiple species after 24 h of hyperoxia, when studied by electron microscopy, demonstrate a diffuse infiltration of activated neutrophils (43). In addition, increases in P-selectin and up-regulation in ICAM-1, a ligand for neutrophil ␤ 2 integrins, have been demonstrated early in the course of hyperoxia exposure, lending further evidence for a neutrophil-mediated injury (44 -47).…”
Section: Discussionsupporting
confidence: 78%
“…Our findings of a significant increase in neutrophil infiltration in hyperoxia-exposed mice complement and extend the conclusions of other studies that found that high concentrations of oxygen led to the release of reactive oxygen species that promoted neutrophil infiltration into the lung (41,42). Lungs taken from multiple species after 24 h of hyperoxia, when studied by electron microscopy, demonstrate a diffuse infiltration of activated neutrophils (43). In addition, increases in P-selectin and up-regulation in ICAM-1, a ligand for neutrophil ␤ 2 integrins, have been demonstrated early in the course of hyperoxia exposure, lending further evidence for a neutrophil-mediated injury (44 -47).…”
Section: Discussionsupporting
confidence: 78%
“…Although the inflammatory response with leukocytic recruitment is important for the effective clearance of invading microorganisms (57-59), a prolonged presence of neutrophils in the lung may cause tissue injury by releasing excessive ROS and hydrolytic enzymes (43,(47)(48)(49). The roles of excessive neutrophilic accumulation in mediating hyperoxiainduced lung injury have been examined in both neonatal and adult animal models (60)(61)(62). The infiltration of neutrophils into the lung is directed by cytokines such as IL-8, one of the most studied cytokines (63).…”
Section: Discussionmentioning
confidence: 99%
“…Since bRSV lesions and immunoreactivity were principally in and around small bronchioles, a pathologist (blinded from the study) randomly selected from lowpower bronchioles within lesions. At higher magnification, a grid [29] was centered over the bronchiole and adjacent tissue with the total number of positive cells and morphological cell-type was recorded (area =440 ×440 µm (10 5.3 µm 2 )). At this same time, counts for syncytial cells and mitosis were performed.…”
Section: Morphometrymentioning
confidence: 99%